KOORDINASI PELAKSANAAN PENERTIBAN USAHA PERTAMBANGAN RAKYAT DI KECAMATAN SINGKEP, KABUPATEN LINGGA - Riana, Nova; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The background this study was the lack of communication between the Department of mines and energy of Lingga District with teachers Police Units and Polres praja (satpol PP) either formally or through meetings of coordination in the implementation of curbing people’s mining venture. Based on the foregoing researchers wishing to conduct a descriptive qualitative research on how coordination efforts curbing people’s mining execution in Singkep and knowing and analyzing the factors that influence the coordination of the implementation of curbing people’s mining venture in singkep.The concept of theory that researchers use is coordination theory according to Hasibuan (2006), who suggested indicators in this research in the Division of duties, discipline, good communication, and unity of action. Researchers use interview techniques and observations with the use of key informants as are Department of mines and energy of Lingga and County through the sampling methods of snowball.Research result can be concluded that the coordination of the implementation of curbing people’s mining venture in singkep is not running optimally, in other words there are still many problems that arise in its implementations. As for the factors that influence the coordination of the implementation of curbing people’s mining venture in Singkep i.e. managerial hierarchy of factors, rules and procedures, planning and goal setting, as well as poverty (economy). All four of these factors greatly affect the implementation coordination efforts in curbing people’s mining in Singkep.Key Words : Coordination, Implementation, Curbing